2000
DOI: 10.1177/004947550003000219
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Qat Chewing on Blood Pressure and Heart Rate in Healthy Volunteers

Abstract: The leaves of the Qat plant (Catha edulis Forsk., Celastraceae) which contain amphetamine like compounds are widely chewed in Yemen and East Africa for their pleasurable stimulant properties. There are also a number of unwanted side-effects and this paper studies the effect on heart rate and blood pressure in 80 healthy volunteers. During a 3-h period of chewing fresh Qat leaves there was a significant and progressive rise in systolic and diastolic blood pressure and heart rate, and levels had not returned to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 5 publications
2
71
0
Order By: Relevance
“…4,5 Several studies have reported increases in heart rate and blood pressure in association with khat chewing. [25][26][27][28][29] In a cross-sectional study of 4001 adults aged 25 and this increase correlated with plasma levels of cathinone. Furthermore, Gugelmann et al 29 reported positive inotropic and chronotropic actions in isolated atria in response to the administration of cathinone.…”
Section: Khat Chewing and Cardiovascular Diseasementioning
confidence: 99%
“…4,5 Several studies have reported increases in heart rate and blood pressure in association with khat chewing. [25][26][27][28][29] In a cross-sectional study of 4001 adults aged 25 and this increase correlated with plasma levels of cathinone. Furthermore, Gugelmann et al 29 reported positive inotropic and chronotropic actions in isolated atria in response to the administration of cathinone.…”
Section: Khat Chewing and Cardiovascular Diseasementioning
confidence: 99%
“…Peripherally, cathinone and cathine are equipotent in the release of noradrenaline at the presynaptic storage sites; thus, both have sympathicomimetic effects. The short-term physiological effects of khat reflect the sympathicomimetic and central dopaminergic activity, e. g. increased heart rate and elevated diastolic and systolic blood pressure (Brenneisen, Fisch, Koelbing, Geisshusler & Kalix, 1990;Hassan et al, 2000;Toennes et al, 2003;Widler et al, 1994). The immediate emotional effects in experimental human settings are euphoria (Brenneisen et al, 1990;Widler et al, 1994) and a subsequent depressive reaction (Hassan, Gunaid, El-Khally & Murray-Lyon, 2002).…”
Section: Chemical Agents Pharmacology and Neurophysiological Effectsmentioning
confidence: 99%
“…There is fairly extensive literature on the potential adverse effects of habitual use of khat on mental, physical, and social well-being (5). Some khat chewers experience anxiety, tension, restlessness, hypnogogic hallucinations, hypomania, and aggressive behaviour or psychosis (6,7).…”
Section: Introductionmentioning
confidence: 99%